Bacteriophage T4 Vaccine Platform for Next-Generation Influenza Vaccine Development - Li, Mengling; Guo, Pengju; Chen, Cen; Feng, Helong; Zhang, Wanpo; Gu, Changqin; Wen, Guoyuan; Rao, Venigalla B.; Tao, Pan (Frontiers in Immunology, 2021)
Developing influenza vaccines that protect against a broad range of viruses is a global health priority. Several conserved viral proteins or domains have been identified as promising targets for such vaccine development. However, none of the targets is sufficiently immunogenic to elicit complete protection, and vaccine platforms that can enhance immunogenicity and deliver multiple antigens are desperately needed. Here, we report proof-of-concept studies for the development of next-generation influenza vaccines using the bacteriophage T4 virus-like particle (VLP) platform. Using the extracellular domain of influenza matrix protein 2 (M2e) as a readout, we demonstrate that up to ~1,281 M2e molecules can be assembled on a 120 x 86 nanometer phage capsid to generate M2e-T4 VLPs. These M2e-decorated nanoparticles, without any adjuvant, are highly immunogenic, stimulate robust humoral as well as cellular immune responses, and conferred complete protection against lethal influenza virus challenge. Potentially, additional conserved antigens could be incorporated into the M2e-T4 VLPs and mass-produced in E. coli in a short amount of time to deal with an emerging influenza pandemic.